Highly Efficient Actuator of Graphene/Polydopamine Uniform Composite Thin Film Driven by Moisture Gradients. Issue 14 (4th May 2016) - He, Jiang; Xiao, Peng; Zhang, Jiawei; Liu, Zhenzhong; Wang, Wenqin; Qu, Liangti; Ouyang, Qing; Wang, Xuefei; Chen, Yousi; Chen, Tao
Abstract : This study demonstrates that uniform materials of reduced graphene oxide/polydopamine composite thin film can serve as a highly sensitive and ultrafast responsive actuator driven by water gradients absorption‐induced in situ formation of bilayer structures in swelling difference along the lateral uniform thin film.